Preparation method of millimeter-scale grain perovskite film

By controlling the reaction of methylamine gas with MAPbI3 perovskite, a perovskite film with millimeter-level grains was prepared, which solved the problems of low efficiency and poor stability caused by film defects in the prior art, and achieved a more efficient and stable perovskite solar cell device.

CN114068821BActive Publication Date: 2025-04-29TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010733861.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-07-27
Publication Date
2025-04-29
Estimated Expiration
2040-07-27

AI Technical Summary

Technical Problem

There are a large number of defects in the thin films of existing perovskite solar cells, resulting in non-radiative recombination of carriers, reducing photoelectric conversion efficiency, and accelerating the decomposition of materials, affecting the stability of the device.

Method used

Perovskite films with millimeter-scale grains were prepared by controlling the reaction of methylamine gas with MAPbI3 perovskites. The method includes spin coating the precursor solution on a porous titanium dioxide substrate and annealing, followed by filling the preheated reactor with methylamine gas, controlling the exhaust time and pressure to form a high-quality millimeter-scale grain perovskite film.

Benefits of technology

The prepared millimeter-scale crystal grain perovskite film has better crystallinity, more concentrated consistent orientation, lower trap state density, and longer carrier life, resulting in higher photoelectric conversion efficiency of the device and better environmental stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114068821B_ABST
    Figure CN114068821B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a millimeter-scale grain perovskite film, firstly, a raw perovskite film is prepared on a porous titanium dioxide substrate using a one-step method, and then the raw perovskite film is treated with methylamine gas to obtain a millimeter-scale grain perovskite film. The preparation method of the invention is simple and easy to implement, and the prepared film has better crystallinity, more concentrated orientation, lower trap state density, longer carrier lifetime, higher device efficiency, and better environmental stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar cell preparation, and in particular, relates to a method for preparing a perovskite film with millimeter-scale grains by controlling the reaction of methylamine gas and MAPbI3 perovskite. Background Art

[0002] With the rapid expansion of the world's population and the rapid development of the economy, the world's energy problems are becoming increasingly prominent. Traditional fossil energy is not only a non-renewable energy source, but also brings serious environmental problems. For the sustainable development of the world economy and the effective improvement of the ecological environment, finding and developing new environmentally friendly renewable energy has become an urgent need for mankind. Solar energy has the advantages of being inexhaustible and not producing greenhouse gas emissions, which has attracted widespread attention. There are many ways to utilize solar energy, including photothermal energy conversion, photovoltaic energy conversion, photobioenergy conversion, and photochemical energy conversion. Among them, directly converting solar energy into electrical energy is of great significance to the development of the entire human society, and can effectively alleviate the current energy shortage and environmental pollution caused by fossil energy power generation. Developing a green and environmentally friendly photovoltaic industry and developing solar cells with high photoelectric conversion efficiency and excellent performance have become major national development strategies and have received widespread attention.

[0003] In recent years, organic-inorganic hybrid perovskite solar cells have developed rapidly, and the photoelectric conversion efficiency of small devices has exceeded 25%. In organic-inorganic hybrid perovskite solar cells, the quality of the perovskite light-absorbing layer directly affects the performance of the final device. Studies have shown that there are a large number of defects on the surface and grain boundaries of perovskite grains. These defects will cause non-radiative recombination of carriers and thus reduce the PCE of the device. At the same time, the decomposition of perovskite materials also starts from defects. Too many defects will accelerate the decomposition of perovskite materials. The grain boundary density in large-grain perovskite films is low, and thus the defect density is also low, which is conducive to improving device performance and stability. Developing new large-grain film processes has become one of the focuses of PSC research. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and to provide a method for preparing a millimeter-scale grain perovskite film in view of the shortcomings of the existing preparation process. Millimeter-scale large grains are prepared by controlling the reaction of methylamine gas and MAPbI3 perovskite.

[0005] The technical purpose of the present invention is achieved through the following technical solutions.

[0006] The method for preparing a millimeter-scale grain perovskite film is carried out according to the following steps:

[0007] Step 1, lead iodide and methylamine hydroiodide are uniformly dispersed in a solvent to form a precursor solution, which is spin-coated on a porous titanium dioxide substrate and annealed to obtain a pristine MAPbI3 film;

[0008] In step 1, during spin coating, the rotation speed is 3000-5000 rpm and the time is 10-30s.

[0009] Step 2, placing the original MAPbI3 film prepared above in a preheated reactor, filling the reactor with methylamine gas, standing it after filling, and then opening the valve to slowly exhaust, controlling the exhaust time to 60±5s, and finally quickly exhausting and passing inert protective gas to purge the reactor to obtain a millimeter-scale grain perovskite film, wherein:

[0010] (1) The preheating temperature of the reactor is 120 degrees Celsius, and the gauge pressure of the methylamine gas is 0.16 MPa. When exhausting, the gauge pressure drops from 0.16 MPa to 0.06 MPa;

[0011] (2) The preheating temperature of the reactor is 140 degrees Celsius, and the gauge pressure of the methylamine gas is 0.2 MPa. When exhausting, the gauge pressure drops from 0.2 MPa to 0.14 MPa;

[0012] (3) The preheating temperature of the reactor is 160 degrees Celsius, and the gauge pressure of the methylamine gas is 0.32 MPa. When exhausting, the gauge pressure drops from 0.32 MPa to 0.26 MPa.

[0013] In step 2, the inert protective gas is nitrogen, helium or argon.

[0014] In step 2, the exhaust time is controlled to be 60±2s.

[0015] In step 2, the filling of methylamine gas in the reactor and the exhaust are controlled by gauge pressure. When methylamine gas is not filled (i.e., the reactor is filled with air), the pressure gauge displays 0 (i.e., the gauge pressure is 0). When methylamine gas is filled, the gas filling amount can be obtained by reading the pressure gauge. When exhausting, the pressure gauge reading can also be used for control. The pressure gauge range is 0-0.6MPa, and the minimum graduation value is 0.02MPa.

[0016] In step 2, after filling with methylamine gas, the reactor is allowed to stand to achieve uniform mixing of the methylamine gas and the air in the reactor, and at the same time, the overall gas atmosphere is raised to the preheating temperature. The standing time is 4-6 minutes.

[0017] The MAPbI3 film prepared according to the above method has a tetragonal phase of perovskite, with a completely preferred orientation in the

[110] direction, and the entire millimeter-scale grain is a complete single crystal.

[0018] The invention also discloses the application of the MAPbI3 film prepared according to the method in a solar cell device.

[0019] Compared with the prior art, the technical solution of the present invention first uses a one-step method to prepare a raw perovskite film on a porous titanium dioxide substrate, and then uses methylamine gas to treat the raw perovskite film and control the process of crystallization after liquefaction to obtain a millimeter-scale grain perovskite film. The preparation method of the present invention is simple and easy to implement, and the prepared film has better crystallinity, more concentrated orientation, lower trap state density, longer carrier lifetime, higher device efficiency, and better environmental stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an optical microscope photograph of a large-grain film prepared at 120° C. in Example 1 of the present invention.

[0021] Figure 2 This is a scanning electron microscope photograph of a large-grain film prepared at 120° C. in Example 1 of the present invention.

[0022] Figure 3 This is the powder XRD spectrum of the large-grain film prepared at 120° C. in Example 1 of the present invention.

[0023] Figure 4 This is the XRD spectrum of the large-grain film prepared at 120° C. in Example 1 of the present invention.

[0024] Figure 5 The rocking curves of the (110) crystal plane of the large-grain film prepared at 120° C. in Example 1 of the present invention and the small-grain film of the comparative example are shown.

[0025] Figure 6 This is an EBSD test picture of the large-grain film prepared at 120° C. in Example 1 of the present invention, wherein a is a back electron image, b is an inverse pole figure in the same area as a, and c is a corresponding scale of color and orientation in the inverse pole figure.

[0026] Figure 7 1. Transmission electron microscope image of the cross section of the large-grain thin film prepared at 120° C. in Example 1 of the present invention and selected area electron diffraction images of three regions thereof.

[0027] Figure 8 This is the synchrotron radiation image of the large-grain film prepared at 120° C. in Example 1 of the present invention (generated by superimposing three photos at θ=0, 7.05, 14.1°).

[0028] Fig. 9 The graphs are UV-visible absorption spectra of the large-grain film (a) prepared at 120° C. in Example 1 of the present invention and the small-grain film (b) of the comparative example.

[0029] Fig.10Steady-state fluorescence spectra of the large-grain film (a) prepared at 120° C. in Example 1 of the present invention and the small-grain film (b) of the comparative example.

[0030] Fig.11 Graphs of transient fluorescence spectra of the large-grain film (a) prepared at 120° C. in Example 1 of the present invention and the small-grain film (b) of the comparative example.

[0031] Fig.12 This is a space charge limiting current curve of the large-grain film prepared at 120° C. in Example 1 of the present invention.

[0032] Fig.13 Graphs of the forward and reverse scanning JV curves of the large-grain film prepared at 120° C. in Example 1 of the present invention, wherein a is the reverse scanning JV curve and b is the forward scanning JV curve.

[0033] Fig.14 It is the IPCE spectrum line diagram of the large-grain film prepared at 120° C. in Example 1 of the present invention, wherein curve a corresponds to the IPCE of the left coordinate, and curve b corresponds to the short-circuit current obtained by integrating the IPCE spectrum of the right coordinate with the wavelength.

[0034] Fig.15 These are the XRD spectra of the large-grain film prepared at 120°C in Example 1 of the present invention and the comparative small-grain film before and after aging, wherein a is the state of the comparative small-grain film before aging, and c is the state of the comparative small-grain film after aging for 200 hours; b is the state of the large-grain film before aging, and d is the state of the large-grain film after aging for 200 hours.

[0035] Fig.16 This is an optical microscope photograph of a large-grain film prepared at 140° C. in Example 2 of the present invention.

[0036] Fig.17 This is an optical microscope photograph of a large-grain film prepared at 160° C. in Example 3 of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0038] Source of medicine:

[0039] PbI2 (lead iodide) was purchased from: Xi'an Biolight Technology Co., Ltd. (purity: 99.99%)

[0040] MAI (methylamine hydroiodide) was purchased from: Xi'an Biolight Technology Co., Ltd. (purity: 99.5%)

[0041] The instruments and models involved in the tests in the embodiments are as follows:

[0042] PANalytical Empyrean diffractometer mainly uses three test methods of XRD diffractometer: 1. Powder test; 2. Thin film test; 3. Rocking curve. The powder test and thin film test have the same settings, with a scanning range of 5-60° and a scanning rate of 5°min. -1 In the rocking curve test, the scanning range is 2-13° for the (110) crystal plane of MAPbI3 crystal. In the embodiment, the sample substrates are all FTO conductive glass coated with porous TiO2 film as porous titanium dioxide substrates, and then the film prepared by the present invention is set; the light source is a 2.2Kw Cu target (wavelength is ).

[0043] Synchrotron radiation data were collected at the 1W1A X-ray scattering station of the Beijing Synchrotron Radiation Center

[0044] Oxford Instruments Symmetry EBSD detector, data analysis software is AZtec and Channel 5 of Oxford Instruments, test conditions are acceleration voltage 20kV, beam current 15nA, single pixel exposure time 1ms.

[0045] Hitachi SU5000 field emission scanning electron microscope; Hitachi S-4800 field emission scanning electron microscope; Hitachi SU8020 field emission scanning electron microscope

[0046] The JEM-2100F transmission electron microscope of Japan Electron was used to obtain selected area electron diffraction (SAED) patterns. In the SAED test, a 50nm aperture was selected.

[0047] A FEI Helios Nanolab G3 CX dual-beam electron microscope was used to prepare cross-section samples for SAED testing (focused ion beam FIB). Ga ions were used as the ion source. A layer of amorphous carbon was first deposited on the sample surface before cutting, and 700nm and 1μm Pt were then deposited step by step to protect the sample. The cross section was first cut with Ga ions at an acceleration voltage of 30kV and a beam current of 0.79nA, and finally polished with an ion beam at an acceleration voltage of 5kV and a beam current of 7pA. Finally, a 70nm thick cross section was obtained.

[0048] Nikon LV100ND Metallographic Microscope

[0049] Shimadzu UV-1800 UV / Vis spectrophotometer, 300-1000nm; blank FTO conductive glass was used for baseline correction before all samples were tested.

[0050] The Edinburgh FLS980 steady-state transient fluorescence spectrometer collects steady-state fluorescence and transient fluorescence data. The steady-state fluorescence spectrum light source is a xenon lamp, and the transient fluorescence spectrum excitation light source is a 485nm laser generator.

[0051] The JV curve test was performed using a Keithley 2400 digital source meter and a 300W collimated xenon lamp as the light source. Before the test, the light intensity was calibrated using a standard silicon solar cell to ensure that the light intensity after calibration was 100mW cm under the AM 1.5G standard. 2 .

[0052] The monochromatic photoelectric conversion efficiency (IPCE) was collected using JASCO's PV-25DYE, using a 300W xenon lamp as the light source.

[0053] The stability test was carried out in a DHS-100 constant temperature and humidity chamber produced by Beijing Zhongke Environmental Testing Instrument Co., Ltd.

[0054] Embodiment 1:

[0055] First, a one-step method was used to prepare the original perovskite film on a porous titanium dioxide substrate: 461 mg of PbI2 and 159 mg of MAI were dissolved in 600 mg of DMF solvent, and then stirred at 60°C for 1 hour to prepare the precursor solution. 30 μl of the precursor solution was added to the prepared porous TiO2 substrate, and then spin-coated at 4000 rpm for 30 seconds. The film was then transferred to a hot plate at 100°C for annealing for 10 minutes. The original MAPbI3 film was prepared, that is, the original MAPbI3 film was formed on the porous titanium dioxide substrate.

[0056] Place the original MAPbI3 film face up (i.e. exposed to the reaction atmosphere) and place it horizontally in a preheated reactor (reactor volume 200ml, preheating temperature 120℃). Fill the reactor with 0.16MPa methylamine gas (pressure gauge range 0-0.6MPa, minimum scale value 0.02MPa, pressure value here is gauge pressure 0.16MPa, i.e. value higher than atmospheric pressure), and let it stand for 5 minutes after filling. Open the valve to exhaust, and exhaust slowly in the range of 0.16MPa-0.06MPa (gauge pressure, i.e. pressure gauge reading), and the exhaust time is 60s (i.e. pressure gauge reading drops from 0.16MPa to 0.06MPa, and it takes 60s). When the pressure in the reactor is lower than 0.06 MPa (gauge pressure), all gases are quickly discharged, and finally N2 is introduced to purge the reactor. The reactor is opened and the sample is taken out to obtain a millimeter-scale grain perovskite film, that is, a millimeter-scale grain perovskite film is formed on a porous titanium dioxide substrate.

[0057] At the same time, the preparation of small-grain thin films was carried out according to the references for comparison: the original MAPbI3 thin film prepared by the one-step method was placed face up in a MAPbI3-filled 0 The sample was quickly taken out and placed in the atmosphere when the film completely turned into a transparent colorless liquid. The preparation was completed when the color of the film completely turned into a dark color [Zhou Z, Wang Z, Zhou Y, et al. Methylamine-Gas-Induced Defect-Healing Behavior of CH3NH3PbI3 Thin Films for Perovskite Solar Cells [J]. Angewandte Chemie International Edition, 2015, 54 (33): 9705-9709].

[0058] from Figure 1 Optical microscopy can clearly show that the film is composed of millimeter-sized square grains, and the surface of the grains has obvious square textures. Further electron microscopy observation also observed that the film is composed of millimeter-sized grains with smooth surfaces ( Figure 2 ).from Figure 3 It can be seen that the prepared large-grain film is a tetragonal phase of MAPbI3 perovskite, and no decomposition or phase transition occurs. Figure 4 The obtained large grain film has a strong diffraction peak and the film is completely preferentially oriented in the

[110] direction. The rocking curve test of a single large grain is further performed, and the results are as follows: Figure 5 As shown in Figure 2. From the rocking curve, it can be seen that the crystallinity of large grains is very good, with a half-peak width of only 0.34°, close to that of single crystals, while the half-peak width of the rocking curve of the small grain film reaches 4.2°, which is an order of magnitude higher than that of the large grain film. The rocking curve results show that the crystallization quality of large grain films is qualitatively improved compared to small grain films.

[0059] like Figure 6 As shown in the figure, a is the back electron diffraction image of the large grain film. It can be seen that the back electron diffraction image is consistent with the optical image and the SEM image; b is the inverse pole figure of the same area analyzed based on the back electron diffraction signal. The different brightness on the figure represents different orientations. For the specific corresponding relationship, see c. From b, it can be seen that the brightness inside the same grain is uniform, indicating that its crystallinity is good and the internal orientation is consistent.

[0060] from Figure 7It can be seen that there is no obvious grain boundary in the radial direction of the large-grain film, and the electron diffraction test at three positions in the radial direction shows that the diffraction pattern also presents a lattice, indicating that the grain is a complete whole in the radial direction (selecting 3 points on the left image for selected area electron diffraction, the result is shown in the right image, selecting 3 points on the cross section for selected area electron diffraction, and the selected area electron diffraction image corresponds to the standard points). Figure 8 The two-dimensional diffraction patterns of a single large grain at θ = 0, 7.05 and 14.1° are shown. When θ = 0°, there is only a straight spot on the detector. When θ = 7.5°, diffraction points of the (110) crystal plane appear on the detector, and the diffraction points are almost not divergent. Similar results were obtained when θ = 14.1°. In the entire test results, no diffraction rings were observed for polycrystalline films, and the diffraction spots were relatively concentrated. The synchrotron radiation test results further prove that the entire large grain is a complete single crystal, and the crystal quality of the grain is high, which is consistent with the previous EBSD and rocking curve results.

[0061] from Fig. 9 It can be seen that the light absorption of the large-grain film is significantly enhanced compared with the small-grain film. Fig.10 The fluorescence peak intensity of the medium-large grain film is 98 times that of the small grain film, and the fluorescence peak position is 12nm blue-shifted. The difference of two orders of magnitude in fluorescence intensity indicates that the crystallinity of the large grain film is improved, resulting in a reduction in surface defects. At the same time, the blue shift of the fluorescence peak can draw similar conclusions. Time-resolved photoluminescence spectroscopy (TRPL) was performed on the two films, and the results are shown in the figure. Fig.11 As shown. After exponential function fitting, the average carrier lifetime of the large-grain film is τ = 271ns, while the average carrier lifetime of the small-grain film is only τ = 29ns. The longer carrier lifetime in the large-grain film indicates that there are fewer surface defect sites in the large-grain film and the carrier recombination is slow, which is consistent with the conclusion of the steady-state fluorescence spectrum. The fluorescence spectrum results show that the high crystallinity and low grain boundary density of the large-grain film significantly reduce the non-radiative recombination of photogenerated carriers in the film.

[0062] from Fig.12 It can be estimated that the defect state density of large grain film is approximately 9.7×10 13 cm -3 The defect state density of the large-grain film is about 2 orders of magnitude lower than that of the traditional small-grain film. The large-grain film is applied to solar cell devices. Fig.13 As shown in Figure 1, a is the reverse scanning JV curve of the large grain film, with a photoelectric conversion efficiency of 22.31%, a fill factor of 0.796 and a short-circuit current of 23.65 mA / cm -2, the open circuit voltage is 1.185V; b is the forward scanning JV curve of the large grain film, its photoelectric conversion efficiency is 22.11%, the fill factor is 0.79, and the short circuit current is 23.68mA / cm -2 , the open circuit voltage is 1.182V. Fig.14 It can be seen that the spectral effect range of the large-grain film is 300-785nm, which is consistent with the UV-visible light absorption spectrum, and the final integration gives J SC 23.48 mA / cm -2 , which is consistent with the IV curve result. Curve a corresponds to the IPCE of the left coordinate, and curve b corresponds to the short-circuit current obtained by integrating the IPCE spectrum with the wavelength on the right coordinate. The present embodiment and the comparative example were subjected to aging tests under the following aging conditions: room temperature 20-30 degrees Celsius, 65% humidity, as shown in the attached Fig.15 As shown, the inverted triangle represents the diffraction peak of MAPbI3 perovskite, the regular octagon represents the diffraction peak of the decomposition product PbI2, and the pentagon represents the diffraction peak of the hydrate of MAPbI3 perovskite. It can be seen that after 200 hours of aging, the peak of lead iodide in the large-grain film is very weak, and the diffraction peak of MAPbI3 perovskite is still dominant, indicating that the stability of the large-grain film is very good; in comparison, the small-grain film of the comparative example has a large amount of lead iodide after the same aging time, and its stability is poor.

[0063] Example 2

[0064] First, the original perovskite film was prepared on a porous titanium dioxide substrate using a one-step method: 461 mg of PbI2 and 159 mg of MAI were dissolved in 600 mg of DMF solvent, and then stirred at 60°C for 1 hour to prepare the precursor solution. 30 μl of the precursor solution was added to the prepared porous TiO2 substrate, and then spin-coated at 4000 rpm for 30 seconds. The substrate was then transferred to a hot plate at 100°C for annealing for 10 minutes, and the original MAPbI3 film was prepared.

[0065] Place the original MAPbI3 film face up and horizontally in a preheated reactor (reactor volume 200ml, preheating temperature 140℃). Fill the reactor with 0.2MPa methylamine gas (pressure gauge range 0-0.6MPa, minimum scale value 0.02MPa), and let it stand for 5 minutes after filling. Open the valve and slowly exhaust at 0.2MPa-0.14MPa, and the exhaust time is 60s. When the pressure in the reactor is lower than 0.06MPa, quickly exhaust all gases, and finally pass N2 to purge the reactor, open the reactor and take out the sample.

[0066] Fig.16The optical microscope image of the large-grain film prepared at 140°C is shown in the figure, which is basically consistent with the morphology of the film prepared at 120°C, and the testing shows that the performance is basically similar to that of the film.

[0067] Example 3

[0068] First, the original perovskite film was prepared on a porous titanium dioxide substrate using a one-step method: 461 mg of PbI2 and 159 mg of MAI were dissolved in 600 mg of DMF solvent, and then stirred at 60°C for 1 hour to prepare the precursor solution. 30 μl of the precursor solution was added to the prepared porous TiO2 substrate, and then spin-coated at 4000 rpm for 30 seconds. The substrate was then transferred to a hot plate at 100°C for annealing for 10 minutes, and the original MAPbI3 film was prepared.

[0069] Place the original MAPbI3 film face up and horizontally in a preheated reactor (reactor volume 200ml, preheating temperature 160℃). Fill the reactor with 0.32MPa methylamine gas (pressure gauge range 0-0.6MPa, minimum scale value 0.02MPa), and let it stand for 5 minutes after filling. Open the valve and slowly exhaust at 0.32MPa-0.26MPa, and the exhaust time is 60s. When the pressure in the reactor is lower than 0.06MPa, quickly exhaust all gases, and finally pass N2 to purge the reactor, open the reactor and take out the sample.

[0070] Fig.17 The optical microscope image of the large-grain film prepared at 160°C is shown in the figure, which is basically consistent with the morphology of the film prepared at 120°C, and the testing shows that it has basically similar properties.

[0071] According to the content of the present invention, the process parameters are adjusted to achieve the preparation of millimeter-scale grain perovskite films, and the performance is basically consistent with the present invention after testing. The above is an exemplary description of the present invention. It should be noted that any simple deformation, modification or equivalent replacement that can be made by other technicians in this field without spending creative labor falls within the protection scope of the present invention without departing from the core of the present invention.

Claims

1. Millimeter-scale grain perovskite film, characterized in that: The millimeter-scale grain perovskite film is a MAPbI3 film, which has a tetragonal phase of perovskite and is completely preferentially oriented in the [110] direction. The entire millimeter-scale grain is a complete single crystal. Follow the steps below: Step 1, lead iodide and methylamine hydroiodide are uniformly dispersed in a solvent to form a precursor solution, which is spin-coated on a porous titanium dioxide substrate and annealed to obtain a pristine MAPbI3 film; Step 2, placing the original MAPbI3 film prepared above in a preheated reactor, filling the reactor with methylamine gas, standing it after filling, and then opening the valve to slowly exhaust, controlling the exhaust time to 60±5s, and finally quickly exhausting and passing inert protective gas to purge the reactor to obtain a millimeter-scale grain perovskite film, wherein: (1) The preheating temperature of the reactor is 120 degrees Celsius, and the gauge pressure of the methylamine gas is 0.16 MPa. When the gas is slowly exhausted, the gauge pressure drops from 0.16 MPa to 0.06 MPa; (2) The preheating temperature of the reactor is 140 degrees Celsius, and the gauge pressure of the methylamine gas is 0.2 MPa. When the gas is slowly exhausted, the gauge pressure drops from 0.2 MPa to 0.14 MPa; (3) The preheating temperature of the reactor is 160 degrees Celsius, and the gauge pressure of the methylamine gas is 0.32MPa. When the gas is slowly exhausted, the gauge pressure drops from 0.32MPa to 0.26MPa.

2. The millimeter-scale grain perovskite film according to claim 1, characterized in that: In step 1, the spin coating is performed at a speed of 3000-5000 rpm and a time of 10-30 s.

3. The millimeter-scale grain perovskite film according to claim 1, characterized in that: In step 2, the inert protective gas is nitrogen, helium or argon.

4. The millimeter-scale grain perovskite film according to claim 1, characterized in that: In step 2, the exhaust time is controlled to be 60±2s.

5. The millimeter-scale grain perovskite film according to claim 1, characterized in that: In step 2, the filling of methylamine gas in the reactor and the exhaust are controlled by gauge pressure.

6. The millimeter-scale grain perovskite film according to claim 1 or 5, characterized in that: The pressure gauge range is 0-0.6MPa, and the minimum division value is 0.02MPa.

7. The millimeter-scale grain perovskite film according to claim 1, characterized in that: In step 2, after filling with methylamine gas, the mixture is allowed to stand for 4 to 6 minutes.

8. Use of the millimeter-scale grain perovskite film according to any one of claims 1 to 7 in a solar cell device.

Citation Information

Patent Citations

  • Novel method for improving quality of perovskite

    CN106159097A

  • A method for fabricating solar cell light-absorbing layer based on single crystal transfer method and its application

    CN109088003A